Vehicular Ad-Hoc Network Performance with Different Routing Protocol Approaches: A Review - More, Aayushi; Agrawal, Shikha; Ahirwar, Manish (International Journal of Computer Sciences and Engineering, 2019)
The basic concept in Vehicular Ad hoc Network is to integrate and fuse the mobile vehicles on road into an ad hoc network to enable communication among the vehicles on the move. The ad hoc network is infrastructure less and do not have any centralized administration. As a result, every individual node in VANETs act as a router in transmitting the packets from source towards the respective destinations. But, the delivery of packets is not always assured. Sometimes there is a possibility of high loss of packets due to adversarial conditions. Because of the high mobile nature of the nodes in VANETs, there could be frequent link failures resulting in high packet drops. In this paper the survey of different kinds of clustering algorithm have done and find best algorithm for VANET and studied different kinds of parameters.